Synthesis, structure and properties of novel Cu(II)-based metal-organic frameworks - Bardini, Marco (Department of Chemistry, 2020)
Porous crystalline materials are known to be useful for a number of applications, including sensing, 1 drug delivery, 2 solid state catalysis3 and controlled absorption and release of liquids, gases and small molecules in solution. 4,5 Within this general definition, a class of materials that has seen its importance grow exponentially in the past two decades has been that of the Metal-Organic Frameworks, or MOFs. These materials have shown a lot of potential, especially in devices aimed at sequestering greenhouse gases (such as CO2 and CH4) from the atmosphere, 6 as well as in fuel tanks for hydrogen-powered cars. 7 The characteristics that allow MOFs to be used for such purposes are their high internal surface area to volume ratio, their relatively high thermal stability and the possibility to fine-tune their structure to optimize a given MOF for a given application. 8 Another feature of some MOFs, especially those built with semiflexible organic linkers9 between metallic nodes, is that they can change their conformation and therefore their pore size and internal surface area, in response to an external stimulus. 2,10 This behavior is especially interesting for systems which can be engineered to absorb and then release small molecules in a controlled manner. 11,12 This last property is one that I set out to exploit in my thesis work, starting from Cu(II) molecular complexes previously synthesized in the University of Cape Town (UCT) laboratories and varying experimental conditions in order to get MOFs of similar systems. Thus, this work will mainly describe the several novel crystal structures I obtained during my research. Each chapter will also discuss the basic spectroscopic and thermal properties of the material explored therein. Of these crystals, two are novel Cu(II)-based coordination polymers, which were named 1-MBUCT and 2-MBUCT, with seldom-seen coordination characteristics and other interesting features, including solvent-filled cavities within their crystal structure, which makes them promising candidates to be fully considered MOFs. After exploring the synthesis and structure of the materials, this work will mainly focus on determining whether the cavities inside 1-MBUCT and 2-MBUCT are accessible to other guests, without disrupting the overall morphology of the material. This was done through solvent exchange experiments, which were inconclusive but nonetheless suggested that these materials did indeed retain their shape, while allowing guest molecules inside their pores, thus being worthy of being described as MOFs. 6 All other structures are byproducts obtained during various attempts to optimize the synthesis of these MOFs, and are often examples of unusual compound classes in their own right. The first of these compounds is a Cu-based [12]crown-6 cyclical compound in which two monomethyl sulfide anions for every copper ion act as bridging ligands within the ring-like structure of the molecule, while the second is a discrete molecular complex formed by two 2,6- pyridinedicarboxylic acid molecules chelating a Cu(II) ion. The main point of interest of the last byproduct, instead, is not its structure, but rather the fact that all the carboxylic acid groups of the 3,5-pyridinedicarboxylic acid molecules included in the complex were subject to an esterification reaction. Such a reaction was unexpected, as the components of this system did not correspond to those found in any reported esterification reaction performed on 3,5-pyridinedicarboxylic acid.